Armed, prohibited and violent at home: implementation and enforcement of restrictions on gun possession by domestic violence offenders in four U.S. localities - Frattaroli, Shannon (Journal of family violence, 2021)
Firearms increase the risk of lethality in violent intimate relationships. Policies that restrict access to firearms by respondents to civil domestic violence protective orders (DVROs) are associated with reductions in intimate partner homicide, yet there is scant literature about how such prohibitions are implemented. We document how four localities are implementing gun possession prohibitions that result from civil and criminal restraining orders and domestic violence misdemeanor convictions; and assess the findings in the context of Kingdon’s agenda setting framework. We identified four jurisdictions where gun dispossession of prohibited domestic violence offenders was underway and collected data through in-depth interviews, site visits, and documents. We coded the data, identified explanatory themes, and compared the findings to Kingdon’s framework. The four jurisdictions have policies ranging from no state laws restricting domestic violence offenders’ access to guns to comprehensive state laws. We describe implementation initiatives to dispossess prohibited people of their guns in the four jurisdictions, two distinct implementation models through which gun dispossession occurs, and an expanded application of Kingdon’s model. In each jurisdiction, we identified one or more individuals who championed implementation. Policies that prohibit domestic violence offenders from possessing guns are promising, and possible in diverse settings and jurisdictions. Here we provide insight into implementation efforts in four jurisdictions, emphasize the role of individuals in prioritizing implementation, and highlight the potential to realize these restrictions across states with different laws. Focusing on implementation is a much-needed paradigm shift that complements the traditional focus on passing domestic violence prevention laws.